Compressive strength and drying shrinkage of fly ash-bottom ash-silica fume multi-blended cement mortars - Watcharapong Wongkeo (2018)
This paper studies the physical properties, compressive strength and drying shrinkage of multi-blended cement under different curing methods. Fly ash, ground bottom ash and undensified silica fume were used to replace part of cement up to 50% by weight. Specimens were cured in air at ambient temperature, water at 25, 40 and 60 °C, sealed with plastic sheeting for 28. days. The results show that absorption and volume of permeable pore space (voids) of blended cement mortars at 28. day under all curing methods tend to increase with increasing silica fume replacement. The compressive strength of blended cement with fly ash and bottom ash was lower than that of Portland cement control at all curing condition while blended cement with silica fume shows higher compressive strength. In addition, the compressive strength of specimens cured with water increased with increasing curing temperature. The drying shrinkage of all blended cement mortar cured in air was lower than that of Portland cement control while the drying shrinkage of blended cement mortar containing silica fume, cured with plastic sealed and water at 25 °C was higher than Portland cement control due to pore refinement and high autogenous shrinkage. However, the drying shrinkage of blended cement mortar containing SF cured with water at 60 °C was lower than that of Portland cement control due to lower autogenous shrinkage and the reduced microporosity of C-S-H. © 2011.